Bradyarrhythmias in patients with COVID‐19: Marker of poor prognosis?. Issue 10 (14th September 2020) - Chinitz, Jason S.; Goyal, Rajat; Harding, Melissa; Veseli, Granit; Gruberg, Luis; Jadonath, Ram; Maccaro, Paul; Gandotra, Puneet; Ong, Lawrence; Epstein, Laurence M.
Abstract: Background: Despite descriptions of various cardiovascular manifestations in patients with coronavirus disease 2019 (COVID‐19), there is a paucity of reports of new onset bradyarrhythmias, and the clinical implications of these events are unknown. Methods: Seven patients presented with or developed severe bradyarrhythmias requiring pacing support during the course of their COVID‐19 illness over a 6‐week period of peak COVID‐19 incidence. A retrospective review of their presentations and clinical course was performed. Results: Symptomatic high‐degree heart block was present on initial presentation in three of seven patients (43%), and four patients developed sinus arrest or paroxysmal high‐degree atrioventricular block. No patients in this series demonstrated left ventricular systolic dysfunction or acute cardiac injury, whereas all patients had elevated inflammatory markers. In some patients, bradyarrhythmias occurred prior to the onset of respiratory symptoms. Death from complications of COVID‐19 infection occurred in 57% (4/7) patients during the initial hospitalization and in 71% (5/7) patients within 3 months of presentation. Conclusions: Despite management of bradycardia with temporary (3/7) or permanent leadless pacemakers (4/7), there was a high rate of short‐term morbidity and death due to complications of COVID‐19. The association between new‐onset bradyarrhythmias and poor outcomes may influence management strategies for acutely ill patients with COVID‐19.